The Concept of Islamic Education for Early Childhood as an Effort to Cultivate Morals - Oktio Frenki Biantoro; M. Akhsanudin (Al-Munawwarah: Journal of Islamic Education, 2025)
ABSTRACT Early age is a golden age for child development, where moral education is very important to be formed from the beginning. At this stage, children have a natural tendency to recognize and understand moral values, which greatly influence their character and behavior in the future. However, the challenges in moral education in the family and community environment are still problems that need to be overcome, considering the many cases of deviant behavior among children and adolescents today. This study aims to examine the concept of Islamic education in early childhood as an effort to instill morals. The method used in this study is a qualitative approach with a literature study, which collects and analyzes literature related to this theme. The results of the study show that moral education can be carried out through several methods, including verbal communication, habituation, and storytelling, which are effective in instilling moral values ​​in early childhood. The instillation of morals carried out from an early age has been proven to form positive character in children, develop discipline, and strengthen children’s spiritual relationship with God. Cooperation between parents and educators is very important to create an environment conducive to the formation of good morals. The contribution of this research is to provide insight for parents and educators in implementing effective moral instillation methods in the family and educational environment.